Optical investigations of thermostimulated changes in an ensemble of CdSxSe₁₋x quantum dots embedded into borosilicate glass matrix - Kunets, V.P.; Yukhymchuk, V.O.; Valakh, M.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
We have employed the absorption and Raman spectroscopies to study thermostimulated changes in an ensemble of CdSXSe₁₋X quantum dots embedded into a borosilicate glass matrix. It is shown that additional annealing of the sample containing CdSXSe₁₋X quantum dots leads to growth of the new ones with higher Se content and average radius approximately equal to the previous value. The conclusion was made that the new particles were grown due to diffusion of Cd, S and Se atoms from a glass matrix which was still remained in the oversaturated state, i.e. the recondensation growth stage (so-called “Ostwald ripening” or “diffusion-limited aggregation”) was not achieved during the annealing process. Some parameters of the dots were determined.